Intracranial Hemorrhage in Patients With Hemophilia A - Nugroho Setia Budi; Prananda Surya Airlangga; Bambang Pujo Semedi (Faculty of Medicine-Universitas Airlangga, 2020)
Introduction: Intracranial hemorrhage in inherited bleeding disorders is a medical emergency. The location of bleeding in most children is subdural and the most common cause is hemophilia. Although intracranial bleeding that occurs in people with hemophilia ranges from less than 5% of events, it is a life-threatening medical emergency so appropriate treatment is needed. Case Report: A boy patient 11 years old, 20kg weights have a seizure at home and followed by a decrease in consciousness. It was founded abnormalities in the form of anemia, prolonged FH (PPT 4x and APTT 4x), and hypocalcemia. The patient then was given main therapy; FVIII 100 IU/dL according to the FVIII target level calculated. The therapy continued with 500IU/12 hours according to the daily target of FVIII 50IU/dL. Discussion: The patient's condition was getting better day by day. The patient's consciousness started to improve after 14 days of postoperative. One month after that, the patient received koate treatment as the episodic handler. Diagnosing the exact cause in patients who have intracranial hemorrhage provides appropriate management so that the patients could be helped. Conclusion: Good collaboration between anesthesiologists, neurosurgeons, and pediatrics will increase the probability of successful management of critical bleeding without major sequelae.